Hydrological modeling of chaqchaq ungauged watershed using Arcswatmodel - Ziboon, Abdul Razzak T.; Abdulrahman, Kawa Z.; Arif, Shelan E. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this study sediment and rainfall-runoff models have been developed for the Chaqchaqungauged watershed using Arc SWAT and remotely sensed satellite image. The model aims at simulating the sediment and the runoff into the proposed Chaqchaq dam reservoir near Sulaimani governorate. Field data about the soil cover are collected using 32 soil samples from different locations within the watershed. Five major types of land covers were recognized and represented in the form of raster images of 30*30m resolution namely; Agricultural Land Cropland and pasture (RNGE), Mixed Rangeland (RNGB), Agricultural Orchards (ORCD), Barren Land Exposed Rock Land cover and Mixed Forest Land cover. The predicted annual sediment volume was 5.33 t/ha and the annual runoff depth predicted by this model was 99.17 mm.
Keywords: GIS Remote Sensing Arc SWAT Watershed Area; Surface runoff